Towards a phylogenetic classification of the climbing fern genus Arthropteris. Issue 4 (27th December 2018) - Liu, Hong-Mei; Jiang, Ri-Hong; Guo, Jian; Hovenkamp, Peter; Perrie, Leon R.; Shepherd, Lara; Hennequin, Sabine; Schneider, Harald
Abstract: We inferred the classification of the Paleotropical climbing fern genus Arthropteris and its close relative Psammiosorus, a monotypic genus endemic to Madagascar. The classification of these ferns has until now been poorly understood. To address this, we sampled more than half of the species diversity covering the whole range of the genus including the outlying occurrence at the Juan Fernández Islands. To reconstruct phylogenetic relationships, we obtained DNA sequences from up to six plastid genome regions, including coding and non–coding regions, for these two genera and representatives of all families of the eupolypod I clade, with an emphasis on the Tectariaceae. These data were analyzed using maximum parsimony, maximum likelihood, and Bayesian inference. We also obtained divergence time estimates. Three questions were addressed. (1) We established that Arthropteris and Psammiosorus form a well–supported clade representing a separate taxon based on their morphological distinctiveness, phylogenetic relationships, and separation since the Eocene from other accepted families of eupolypod ferns. (2) Psammiosorus was found to be nested within Arthropteris . (3) Our analyses supported recognition of a previously doubted species endemic to the karst regions of southern China and northern Vietnam. As a consequence of our results, we describe the new family Arthropteridaceae and introduce the new combination Arthropteris paucivenia for the Madagascan endemic previously treated under Psammiosorus .